Processing Condition and Properties of Protein Isolates from Mung Bean (Vigna radiata) and Quinoa (Chenopodium quinoa Willd) - Dewi, Desak Putu Ariska Pradnya (Indonesia International Institute for Life Sciences, 2022)
Mung bean and quinoa are good sources of protein from legumes and pseudo cereals respectively. Both sources have relatively high protein content and acceptable amino acids composition. The potential and application of mung bean and quinoa as protein isolates have been discovered in some studies. Several isolation techniques such as wet fractionation (acid-base extraction), micellization, dry fractionation, aqueous separation or combination of some techniques can be used to isolate protein. This review summarized different methods and processing conditions applied during production of mung bean and quinoa protein isolates. Extracting protein from different sources may require different conditions, which results in different compositions and functional properties. Acid-base extraction is the most common method applied in mung bean and quinoa and results in high protein purity and yields. Micellization is an alternative method used in mung bean to produce higher protein content. Dry fractionation is a sustainable option used in quinoa to concentrate protein fractions. Purification methods such as ultrafiltration and aqueous phase separation can be used. Different methods and processing conditions affect functional properties, including solubility, water and oil absorption, emulsification, foaming, thermal properties of isolates, which also affect the suitable application for isolates. Keywords: Protein isolates; Quinoa; Mung bean; Wet fractionation; Dry fractionation